International encyclopedia of dance. - Selma Jeanne Cohen (Oxford University Press, 2004)
Exciting and fascinating, this reference work succeeds in its goal of bringing joy as well as enlightenment" about all forms of dance in all countries of the world. An extremely useful synoptic outline of contents" with nine sections (including "Ritual and Religion" and "Popular Entertainment") enables the user to explore dance in its cultural and social aspects, while topical essays complement the 2,000-plus entries. Heavily illustrated with black-and-white photographs, the encyclopedia captures the fluid movement of dance; with its depth and scope, this outstanding work has carved a well-deserved niche".--"Outstanding Reference Sources : the 1999 Selection of New Titles", American Libraries, May 1999. Comp. by the Reference Sources Committee, RUSA, ALA